Ultra-compact 122GHz Radar Sensor for Autonomous Aircrafts. (2016) - Nava, Federico; Scheytt, Christoph J.; Zwick, Thomas; Pauli, Mario; Göttel, Benjamin; Winkler, Wolfgang
Abstract: In this paper a prototype of an ultra-compact continuous-wave (CW) and frequency-modulated continuous-wave (FMCW) radar system using a highly-integrated radar chip and in-package antennas will be presented. An introduction will be given on the concept of antenna integration for millimeter-wave radar and the advantages of such systems. The radar then will be described in its main components, a 122 GHz Integrated Circuit including in-package antennas as well as the acquisition and processing system realized using flexible printed circuit board (FLEX PCB) technology. Furthermore initial measurements of the radar system will be presented and explained.